(untitled) (MAUSAM, 2004)
Whereas some El Nino years are known to be associated with droughts in some parts of the globe, notably India and south-east Australia, the El Niño effects are probabilistic, affecting only some regions and, not all El Niños are equally effective. Recently, it was observed that Unambiguous ENSOW (El Niño years, in which the Southern Oscillation Index minima and Pacific sea surface temperature maxima occurred in the middle of the calendar year) were better associated with droughts. In this communication, it is checked whether the effectiveness of El Niños was in any way related to suitable timings of the El Niño events (coincident with main rainy seasons) in India and Australia. In general, El Niños active during the main rainy season were associated better with droughts. But some events did not fit this pattern. Also, many years not having El Niños or La Niñas were associated with droughts or floods. Thus, the El Niño/rainfall relationship is rather loose.